Assciation between Cognitive and Social Factors and Metabolic Control Parameters in Patients with Type 2 Diabetes - GÜLSEVEN KARABACAK, BİLGİ (AVES PRESS LTD, 2016)
Objective: This descriptive and cross-sectional study aimed to determine the association between cognitive and social factors and metabolic control parameters in patients with type 2 diabetes. Methods: The patient population comprised 200 patients with diabetes who were admitted to a public hospital in Istanbul. The patient identification form and multidimensional diabetes questionnaire were used for data collection. Data were assessed by using percentage, mean, Spearman's correlation analysis, Mann-Whitney U test, and Kruskal-Wallis test. Results: The mean age of the patients was 52.50 +/- 13.78 years, and 46.5% of patients were women, 74% were married, 42.5% were preliminary school graduates, and 78% lived with their family. While the handicap perception and misguided behavior scores of the multidimensional diabetes questionnaire were below average, the scores of seriousness perception, support perception, self-efficacy, and result expectation were found to be above average. For individuals who were high school/college graduates, who lived with their family, and were regular exercisers, interference and severity perceptions were low, while support, self-efficacy, and result expectation perception were high. There was a positive correlation between age and handicap and seriousness, whereas there was a negative correlation among support, self-efficacy, and result expectation perception. There was a positive correlation between handicap and seriousness perceptions and metabolic control parameters of the multidimensional diabetes questionnaire and a negative correlation existed between support, self-efficacy, and result expectation perceptions and metabolic control parameters. Conclusion: Based on these findings, there was a significant association between cognitive and social factors and metabolic control parameters.
Keywords: Type 2 diabetes; cognitive and social factors; metabolic factors